Leadership as a Factor in Maintaining Quality Assurance in Technology and Vocational Education and Training: A Systematic Literature Review - Quienera Joshua; Supriyanto Supriyanto; Tutin Aryanti; Mervyn Wong Hsin Jyi; Emmanuel Obobi Tettehfio (Universitas Sultan Ageng Tirtayasa, 2023)
This article focuses on the concept of leadership, which involves managing organizations or groups of individuals, particularly in the context of TVET institutions and sectors. Quality assurance, which measures the level of excellence in comparison to similar processes, is crucial in TVET schools to determine competence and global competitiveness. The article aims to explore the impact of leadership on managing quality in vocational schools and examines various aspects considered for quality control. This study utilizes the Systematic Literature Review, and the data was gathered from reputable sources, specifically Google Scholar, encompassing research conducted between 2018 and 2023. The analysis employed rigorous inclusion and exclusion techniques. The selected articles delve into the impact of leadership skills on quality assurance within the context of vocational education. The findings underscore the crucial role of leadership in guaranteeing educator competence, refining curriculum standards, and establishing effective quality control measures.